Comparative performance analysis of portuguese bank branches - Portela, Maria (2010)
The advent of Internet banking and phone banking is changing the role of bank branches from a predominantly transaction-based one to a sales-oriented role. This paper reports on an assessment of the branches of a Portuguese bank in terms of their performance in their new roles in three different areas: Their effectiveness in fostering the use of new transaction channels such as the internet and the telephone, their effectiveness in increasing sales and their customer base, and their effectiveness in generating profits without compromising the quality of service. We have used Data Envelopment Analysis for the assessment, departing from the basic models to accommodate non-radial and nonoriented measures of performance.